Pengaruh perbedaan lantai kandang terhadap performa ayam broiler - Azis Juliana; Imam Suswoyo; Tri Rachmanto Prihambodo (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
This research aimed to evaluate the effect of different floor levels in a multi-tiered housing system on the production performance of broiler chickens at Khaerun Farm, Purwojati District, Banyumas Regency. The research was conducted on 20,000 broiler chickens of the Cobb CP 707 MV strain, reared in a two-tiered house with approximately 10,000 birds per floor. The observed parameters included feed consumption, body weight gain (BWG), final body weight, depletion, and Feed Conversion Ratio (FCR). The study employed an observational method, which was analyzed using a t-test to determine the significance of differences between the floor levels. The results indicated that there were no statistically significant differences (p>0.05) in all performance parameters between the first and second floors. Although there were slight variations in temperature and humidity between the floors, these differences did not significantly affect production performance. These findings suggest that proper housing management can maintain optimal broiler performance regardless of floor level differences in a multi-tiered housing system.